2009
DOI: 10.1089/thy.2007.0303
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transforming Growth Factor Beta in the Regulation of Thyroid Function and Growth

Abstract: Transforming growth factor beta (TGF-beta) exists in nature as three isoforms. They exert their effects by binding to a type II receptor located at the cell membrane. The TGF-beta-type II receptor complex then recruits type I receptor, and this new complex stimulates the phosphorylation of Smads 2 and 3, which are subsequently transferred to the nucleus, where they regulate gene transcription. The thyroid gland expresses the TGF-beta1 gene mRNA and synthesizes the protein, which under physiologic conditions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 96 publications
(92 reference statements)
1
28
0
2
Order By: Relevance
“…TGF-β and activin exert antiproliferative effects in epithelial cells, including follicular thyroid cells (24). However, TGF-β and activin are overexpressed in several carcinomas (17,19,25).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β and activin exert antiproliferative effects in epithelial cells, including follicular thyroid cells (24). However, TGF-β and activin are overexpressed in several carcinomas (17,19,25).…”
Section: Discussionmentioning
confidence: 99%
“…Realtime PCR analyses revealed that iodide increased the mRNA levels of TGFB1 (Fig. 5B), which regulates immune responses and inhibits thyroid growth and function by downregulating thyroid-specific genes, such as SLC5A5, TG, and TPO (40)(41)(42)(43). Iodide also increased annexin-A1 (ANXA1), which is cleaved and released from apoptotic cells and inhibits the activation of monocytes and neutrophils (Fig.…”
Section: Innate Immune Activation Of the Thyroid Is Induced By Iodidementioning
confidence: 99%
“…It has long been well known that TGF-β suppresses growth of normal thyroid follicular epithelial cells [11,12]. However, the effect of TGF-β on thyroid cancer cell behavior is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In the thyroids, as for other tissues, expression of TGF-β ligands and their receptors and their effects on growth of normal cells and established cancer cells have previously been studied [11,12], but yet the effect of TGF-β signaling on early thyroid carcinogenesis remained to be determined. In this current study, therefore, Tgfbr2 floxE2/floxE2 mice were crossed with FSP1-Cre or thyroid peroxidase (TPO)-Cre mice to study the significance of TGF-β signaling in thyroid follicular epithelial cells and surrounding fibroblasts for thyroid early carcinogenesis.…”
Section: Detection Of Genomic Recombination By Pcrmentioning
confidence: 99%